Preparedness of dental clinics for medical emergencies in Riyadh, Saudi Arabia - Mona Al-Hassan; Sakher AlQahtani (Elsevier, 2019)
Aim: To assess knowledge, training of dental staff and the availability of emergency drugs and equipment in dental clinics, Riyadh, Saudi Arabia. Methods: Cross-sectional survey was conducted in a random sample (N: 325) of governmental and private clinics in Riyadh, Saudi Arabia, between June-December 2016. Questions included Dentist's specialty, age, years of experience, knowledge and preparedness to handle ME (level of training, types of emergency drugs and equipment available). Results: One dentist from each clinic filled the questionnaire (100% of the sample), 19% of whom were general dentists. Medical history is taken orally by 86% of respondents before dental treatment and 12% take vital signs every visit.Of the surveyed clinics, 30% didn't have emergency contact numbers available, 78% didn't have an emergency protocol and only 54% have a medical emergency plan with 11% performing periodic office emergency drills.The most available emergency drug and equipment were Aspirin (53%) and Sphygmomanometer (86%). Oxygen delivery device was not available in 90% of the surveyed clinics. Conclusion: There is an alarming inadequacy of clinic/staff preparation to deal with ME. Efforts should be made to increase the awareness of dentists to take needed precautions and prepare their clinics. Keywords: Medical emergencies, Dental clinics, Preparedness